Formulation design, development and validation of lansoprazole ec pellets 12% w/w by using management tools: a study on process variables and their Impact on quality of the product- Paper retracted - VENKATESWARA REDDY BOYA; DR. K. S. SEKHARA RAO (International Journal of Pharma and Bio Sciences, 2018)
The Research was carried out to demonstrate the design, development and validation of Lansoprazole EC Pellets 12% w/w by using management tools. Stomach is a remarkable organ. It secretes a juice that can digest various foods that we eat, but it seldom digests itself. Ulcer: An ulcer is formation of lesion in GIT. The following factors are mainly responsible for occurrence of ulcers which includesimproper intake of food at right time, sleeplessness by stress and bacterial flora present in the stomach such as Helicobacter Pylori. Many of the studies revealed that the overall prevalence of ulcers is 10.5% in men and 9.5% in women in world wide. This stimulated to select ulcer as a disease and to investigate in a better way to find out suitable remedy. One of the most widely used and available drug is Lansoprazole. The reason for selection of this molecule is having less side effects and more Bioavailability (Rate and extent of drug absorption into the systemic circulation). Lansoprazole Enteric Coated Pellets 12% w/w have been taken three different trails namely Formulation-1, Formulation-2 & Formulation-3 by using process variables of HPMC-E5 (Film forming polymer) and Methacrylic acid copolymer (L-30D) (Enteric polymer). In the process of achieving, the anticipated results the management tools have been used efficiently and plentifully. All the three formulations have been tested against Lansoprazole monograph of USP-41 and found satisfactory outcomes. Formulation-3 has been proven with highest quality attributes.